2017
DOI: 10.1177/1541931213602006
|View full text |Cite
|
Sign up to set email alerts
|

Gamification: Current Research and Applications

Abstract: Gamification is the concept of applying game mechanics to non-game activities (Deterding, Dixon, Khaled, & Nacke, 2011). This concept has received a lot of recent interest from industry and many examples have emerged, especially within the fields of business and marketing, but has grown to encompass such varied examples as health care, training, prosocial behavior, and law enforcement. The purpose of this panel is to discuss some current research and applications of the gamification concept from a varied s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 4 publications
0
17
1
Order By: Relevance
“…For example, Aparicio et al (2012) found that positive effects only occur when Mechanics elements are presented in a non-controlling and voluntary setting. Points only increase intrinsic motivation when the reward is the outcome of an achievement (Doherty, Palmer, & Strater, 2017). Mekler, Brühlmann, Tuch, & Opwis (2017) found in a controlled experiment with points and badges -contrary to earlier studies -that points and badges did not affect intrinsic motivation significantly.…”
Section: Hedonic Motivationcontrasting
confidence: 58%
See 3 more Smart Citations
“…For example, Aparicio et al (2012) found that positive effects only occur when Mechanics elements are presented in a non-controlling and voluntary setting. Points only increase intrinsic motivation when the reward is the outcome of an achievement (Doherty, Palmer, & Strater, 2017). Mekler, Brühlmann, Tuch, & Opwis (2017) found in a controlled experiment with points and badges -contrary to earlier studies -that points and badges did not affect intrinsic motivation significantly.…”
Section: Hedonic Motivationcontrasting
confidence: 58%
“…Points, levels and leaderboards promote the competence need only provided they are presented in a noncontrolling and voluntary setting (Aparicio et al, 2012). Points only increases intrinsic motivation when the rewards is the outcome of an achievement (Doherty et al, 2017). Mekler et al (Mekler et al, 2017) found in a controlled experiment with points and badges, contrary to other researches, that points and badges did not affect intrinsic motivation significantly.…”
Section: Hedonic Motivation (Hm)mentioning
confidence: 85%
See 2 more Smart Citations
“…The terminology of Gamification, in many kinds of research, can be best described as the use of game elements in non-gaming objects [8]. The ability to engage on users makes the Gamification famous in various industries [10][11][12][13]. There are many application designs of Gamification, such as points, badges, leaderboards, and many others [14].…”
Section: Literature Reviewmentioning
confidence: 99%